A Comparison of Parent Reports, the Mental Synthesis Evaluation Checklist (MSEC) and the Autism Treatment Evaluation Checklist (ATEC), with the Childhood Autism Rating Scale (CARS) - Rebecca Netson; Andriane Schmiedel Fucks; Andressa Schmiedel Sanches Santos; Lucas Ernesto Pavoski Poloni; Nilson Noboru Nacano; Elielton Fucks; Katarina Radi; William E. Strong; Alice Aparecida Carnaval; María Russo; Rohan Venkatesh; Andrey Vyshedskiy (MDPI AG, 2024)
This study compares two parent reports, the Mental Synthesis Evaluation Checklist (MSEC) and the Autism Treatment Evaluation Checklist (ATEC), with the Childhood Autism Rating Scale (CARS). The ATEC consists of four subscales, as follows: (1) expressive language, (2) sociability, (3) sensory awareness, and (4) health. The MSEC is complementary to the ATEC in measuring complex language comprehension. The parents of 143 autistic children, from 2 to 22 years of age (mean 6.7 ± 5.1 years), completed the MSEC and the ATEC questionnaires and a clinician assessed their CARS score. The CARS score correlated strongly with all parent reports, the complex language comprehension MSEC (r = 0.60, p < 0.0001), expressive language (r = 0.66, p < 0.0001), sociability (r = 0.58, p < 0.0001), sensory awareness (r = 0.71, p < 0.0001), and health (r = 0.53, p < 0.0001), as well as the total ATEC score (r = 0.75, p < 0.0001). The strongest correlation was between the CARS score and the composite of all five parent-reported scores (total ATEC + MSEC, r = 0.77, p < 0.0001). These results suggest a high fidelity of the MSEC and ATEC parent reports and especially of their composite score, total ATEC + MSEC.